Can someone give me a short proof of the identity, $$\sum_{n=1}^\infty\frac{q^nx^{n^2}}{1-qx^{n}}+\sum_{n=1}^\infty\frac{q^nx^{n(n+1)}}{1-x^n}=\sum_{n=1}^\infty\frac{q^nx^n}{1-x^n}$$

up vote 4 down vote accepted

It's just about using geometric series a lot. Indeed, we have

$\sum\limits_{n=1}^\infty\frac{q^n x^{n^2}}{1-qx^n}=\sum\limits_{n=1}^\infty\sum\limits_{k=0}^\infty q^{n+k}x^{n(n+k)}=\sum\limits_{m=1}^\infty\sum\limits_{d\ge m}q^dx^{md}$

and

$\sum\limits_{n=1}^\infty\frac{q^n x^{n(n+1)}}{1-x^n}=\sum\limits_{n=1}^\infty\sum\limits_{k=0}^\infty q^{n}x^{n(n+1+k)}=\sum\limits_{m=1}^\infty\sum\limits_{1\le d<m}q^dx^{md}$.

Therefore,

$\sum\limits_{n=1}^\infty\frac{q^n x^{n^2}}{1-qx^n}+\sum\limits_{n=1}^\infty\frac{q^n x^{n(n+1)}}{1-x^n}= \sum\limits_{m=1}^\infty\sum\limits_{d\ge m}q^dx^{md}+\sum\limits_{m=1}^\infty\sum\limits_{1\le d<m}q^dx^{md}= \sum\limits_{m=1}^\infty\sum\limits_{d=1}^\infty q^dx^{md}$.

However,

$\sum\limits_{n=1}^\infty\frac{q^n x^{n}}{1-x^n}= \sum\limits_{m=1}^\infty\sum\limits_{d=1}^\infty q^dx^{md}$ as well, and we are done.

Your Answer

 
discard

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.